Assessing sex-based differences in postsurgical clinical outcomes after use of del Nido cardioplegia. (27th September 2022) - Honzel, Emily; Nemeth, Samantha; Kazzi, Brigitte E; Kossar, Alexander P; Sun, Jocelyn; Kaku, Yuji; Takeda, Koji; Takayama, Hiroo; Argenziano, Michael; Spellman, Jessica; Miltiades, Andrea; Fung, Kenmond; et al.
Abstract: OBJECTIVES: del Nido cardioplegia is used to pharmacologically arrest the heart during cardiac surgery and decrease reperfusion- and ischaemia-related myocardial injury. Studies have demonstrated the physiological differences between male and female hearts, potentially related to cardiac size or myocyte calcium handling; we aimed to assess for between-sex differences in clinical outcomes after receipt of del Nido cardioplegia. METHODS: Patients who underwent coronary artery bypass or coronary artery bypass graft/valve surgery at our institution using del Nido cardioplegia (January 2014 to December 2019) were included ( n  = 2118). Clinical data were collected retrospectively. After the creation of a propensity-matched cohort ( n  = 1252), multivariable logistic regression was used to analyse binary postoperative outcomes, and a Gamma model was used for a continuous postoperative outcome. Our primary end-point was a composite end-point comprised of 30-day mortality and/or need for a post-bypass mechanical support device. RESULTS: The final cohort included 459 females and 793 males (matched up to 1:2, all standardized mean differences <0.1). Multivariable logistic regression showed that biological sex was not associated with the composite primary end-point (odds ratio = 0.898, P  = 0.779). A Gamma model indicated that there were no sex-related differences in vasoactive-inotropic scores reflecting vasopressor and inotrope usage at the time of patient operating room exit (exp[est] = 1.394, P  = 0.189). CONCLUSIONS: Our findings showed no significant between-sex differences in clinical outcomes after receiving del Nido cardioplegia, suggesting adequate myocardial protection as currently administered. Further research is warranted to elicit if there are sex-based differences between cardioplegic solutions. IRB APPROVAL DATE (PROTOCOL NUMBER): 26 May 2021 (AAAR8359). Abstract : del Nido (DN) cardioplegia, originally intended for the paediatric population, has been shown to be non-inferior or even potentially superior to other cardioplegia alternatives in general adult surgical populations [1].